Evaluation of Indian input to the international nuclear information system database. (1st January 2011) - Kumar, Anil; Prakasan, E.R.; Kadam, Sandeep; Bhaskar, Nita
The study is aimed at analysing the INIS bibliographic records of publications in India during the period 2000–2008. The analysis includes the inputting trend, time-lag, contributing journals, country collaboration, content analysis through the classification and keywords. India has a total number of 14, 697 records input to the database with an yearly average of 1631 records. The timeliness of input is very noteworthy as 29.15% of all articles are input in the same publication year, 52.57% articles are of only one year delay in inputting. Pramana, Journal of Medical Physics, Radiation Protection and Environment are found as the most contributed Indian journals. Scientists from USA, Germany, Japan, etc., are the main contributors. Nuclear physics and radiation physics, specific nuclear reactors and associated plants, particle accelerators, inorganic, organic, physical and analytical chemistry, etc., are main areas of the Indian input.